THE DETERMINING OF CERTAIN ELEMENTS OF THE COGNITIVE-PERCEIVING SPHERE OF MILITARY PERSONNEL OF THE AIR ASSAULT UNITS OF THE ARMED FORCES OF UKRAINE - Kravchenko, K. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
The cognitive-perceiving sphere of the individual has got a crucial load in terms of developing a world model. Among the cognitive processes there’re the sense, perception, memory, contemplation, imagination and attention. The scientificpsychological approach demands an analytical perception of the perception procedures, however in this real psychological life all these processes are combined unified and dependent on the structure and content of the individuals’ personality, its motives, global purpose etc.The cognitive-perceptional sphere of the individual takes an important role in many types of professional activity. The military activity is not an exception. The timely and correct orientation under combat circumstances, the assessment of one’s role and significance, without considering the necessity of taking decisions that could have implications not only for the results of the tasks set, but also the life and health of other military personnel, which is achieved by intense intellectual activity. Additionally, every service men is obliged to clearly understand the algorithm of actions in average situations of service activity, supposed to have the skills of self-regulation of the cognitive functions, sufficient creative potential and the ability to conduct rapid logical analyses of insignificant complications of the situation under the conditions of combat activities.This work presents certain aspects of the cognitive-perceptional sphere of military personnel, namely the peculiarities of contemplating and intellectual capabilities (intellect).The article presents certain results of empirical research, that have been conducted in air-assault units of the Armed Forces of Ukraine in the period from 2019 till 2020. 173 military men – participants of combat activities in the east of Ukraine have taken part in the research. Due to the fact that the conducted research was vast and broad in terms of volume its results shall be highlighted in a number of scientific publications.The purpose of this particular part of research is to determine certain elements of the cognitive-perceptional sphere, that are typical to the finest military men of the air assault troops. The research is constructed in the following manner. It contained two fields of activity: the first one was the conduct of diagnosis methods with military personnel; the second one was the conduct of a survey among the direct commanders of this military personnel with the aim to identify the example group. The necessity to identify the example group was dictated by the following: determining of a certain number of individuals among the general amount of those that are under research, the psychological features of which are going to be determined as the best and necessary to assure the effective implementation of combat tasks. The survey among direct commanders contained only one single question: « Who of your subordinates could be characterized as a serviceman that has been effective in terms of carrying out tasks in the combat area”. Here is of utmost importance to stipulate the exercise of combat activities, and no other features, as good discipline, healthy working atmosphere etc. The first example group included 18 military men, whilst the second included – 155.By indicating the example group and the further comparison of the features with another group, the purpose that has been set by the researchers has been achieved.The results of the research conducted could be used when determining the candidates to continue service in the air-assault troops of the Armed Forces of Ukraine under the conditions that some of the changes are to be added to the Instruction on organizing the professional-psychological selection in the Armed Forces of Ukraine. Also when receiving the results, the military psychologists could use in terms of internal activities (psychological training and psycho correctional events) in order to achieve the finest results by the military personnel as the representatives of their military branch.
Keywords: military men, air assault troops, the cognitive-perceptional sphere, intellectual capabilities, type of contemplation, style of contemplation, participants of combat activities, psychological features, the operation of the United Forces, professionalpsychological selection